Pola Komunikasi Keluarga Buruh Migran di Desan Pandan Wangi Kecamatan Jerowaru Kabupaten Lombok Timur - Prihartiningsih Prihartiningsih; Agus Purbathin Hadi; Diyah Indiyati (JCommsci - Journal Of Media and Communication Science, 2018)
Migrant worker children left by one or both parents need to observe, the role of the missing father / mother in the family will certainly feel different compared to a complete family member of the family, children who live with fathers without mothers and children who live with you without father or child who lives with a grandmother without a mother and father we need to know. In this study consisted of three families of migrant workers left by both parents, abandoned by Father, and left by the mother in Pandan Wangi Village, Jerowaru District, East Lombok Regency. The purpose of this study was to find out how the communication patterns of migrant workers' families and children's communication behavior in the families of migrant workers in Pandan Wangi Village, Jerowaru District, East Lombok Regency. The research was conducted using a research method through a descriptive approach with qualitative data. The results of the research showed in the families of migrant workers left by one of their parents mother / father applying a family communication pattern that leads to unbalanced split patterns which are unequal separate relationships, where one person in the wife / husband's family dominates.